2011
DOI: 10.1111/j.1365-2249.2010.04308.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated blood levels of inflammatory monocytes (CD14+CD16+) in patients with complex regional pain syndrome

Abstract: SummaryComplex regional pain syndrome (CRPS) is a chronic pain disorder. Although its pathophysiology is not completely understood, neurogenic inflammation is thought to play a significant role. Microglia and astrocytes are activated following tissue injury or inflammation and have been reported to be both necessary and sufficient for enhanced nociception. Blood-borne monocytes/ macrophages can infiltrate the central nervous system (CNS) and differentiate into microglia resulting in hypersensitivity and chroni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 50 publications
(63 reference statements)
2
42
0
1
Order By: Relevance
“…This subgroup might be a better target for trials of immunomodulatory agents. In addition to altered plasma cytokine levels, other significant changes reported in people with CRPS include altered levels of plasma amino acids, 41 serum and saliva antioxidative parameters, 11 blood levels of inflammatory monocytes, 31 and altered intestinal microbial communities. 29 These markers might help define subgroups amenable to specific treatments.…”
Section: Crps Pi-nrs Summary Of Change From Baseline At Week 12 In Obmentioning
confidence: 98%
“…This subgroup might be a better target for trials of immunomodulatory agents. In addition to altered plasma cytokine levels, other significant changes reported in people with CRPS include altered levels of plasma amino acids, 41 serum and saliva antioxidative parameters, 11 blood levels of inflammatory monocytes, 31 and altered intestinal microbial communities. 29 These markers might help define subgroups amenable to specific treatments.…”
Section: Crps Pi-nrs Summary Of Change From Baseline At Week 12 In Obmentioning
confidence: 98%
“…We show that the adherent monocytes in our study are strongly enriched in the CD14dimCD16+ monocyte subset. This subset, which represents only about 10% of the total monocyte population in healthy human blood, is shown to be strongly increased in acute inflammatory conditions like sepsis, autoimmune diseases like rheumatoid arthritis and diabetes and in conditions accompanied by chronic pain [20][21][22] . It has also been proposed that CD14dimCD16+ monocytes develop from classical CD14high monocytes [23] and exhibit a greater ability to adhere to endothelium [24] .…”
Section: Discussionmentioning
confidence: 99%
“…14,19,20,22,23 Only 2 studies compared the levels of inflammatory factors in the affected and the unaffected limbs. These found that the levels of IL-6, 2 IL-1b, 2 TNFa, 2 NPY, 2 PGE2, 2 and CGRP 2,17 were not significantly different between the affected and the unaffected limb.…”
mentioning
confidence: 99%
“…23 Healthy controls were utilized by most studies, [14][15][16][17][19][20][21][22] with the exception of 2 that used subjects with fractures or osteoarthritis, 18 and the unaffected arm 2 as controls. The results are presented in figures 2 and 3.…”
mentioning
confidence: 99%
See 1 more Smart Citation